FORMULATION AND OPTIMIZATION OF FLOATING TABLETS OF CLOPIDOGREL BISULPHATE USING DESIGN OF EXPERIMENTS - Deshkar, Sanjeevani S.; Pawara, Arvind S.; Shirolkar, Satish V. (International Journal of Applied Pharmaceutics, 2018)
Objective: The present study aimed at designing of floating matrix tablet of clopidogrel bisulphate by design of experiments. Methods: The tablets were prepared by direct compression technique using hydroxypropyl methylcellulose K15 (HPMC) as a matrix polymer and sodium bicarbonate as a gas generating agent. In order to optimize the concentration of HPMC (X1) and sodium bicarbonate (X2), a 32 full factorial design was employed. The tablet formulations were evaluated for floating lag time (Y1), floating or buoyancy time (Y2), percent water uptake, and differential scanning calorimetry (DSC) and in vitro drug release (Y3). Results: The formulation variables, HPMC concentration, and sodium bicarbonate concentration exerted a significant effect on floating behavior and drug release characteristics of the tablet. The optimized formulation, with 15% sodium bicarbonate concentration and 30 % HPMC concentration resulted in 5±2.6 sec of floating lag time, 22.0±0.6 h of floating time and 42.0±0.99% of clopidogrel bisulphate release in 8 h of dissolution study. The drug release mechanism was identified as nonfickian. The water uptake studies revealed that with an increase in HPMC concentration, there was an increase in swelling index of tablet whereas higher sodium bicarbonate concentration supported the faster erosion of matrix tablets. DSC study revealed no interaction of drug and polymers. The lower percentage error between predicted and observed responses of the optimized formulation validated the design. Conclusion: The study demonstrated successful designing of floating clopidogrel bisulphate tablet with factorial design.